Vocational High School Entrepreneurship Learning Management Model based on Local Wisdom Products - Sherly Sherly; Kisno Kisno; Adam KeÅ¡ner (Yayasan Keluarga Guru Mandiri, 2023)
Entrepreneurship is a critical activity in driving economic development, and entrepreneurial talents and qualities align with the 4.0 Industrial Revolution and its impact on the economic sector. However, the implementation of Creative Projects and Entrepreneurship in Vocational High School (VHS) subjects tends to be theoretical and unrelated to societal problems. This study intends to develop a model of entrepreneurship learning management for VHS based on local wisdom products. A preliminary study, initial product creation, and initial product test using expert and practitioner validity, limited test, final product test using quasi-experiment, dissemination, and implementation were some of the techniques used to implement a research and development design. The study discovers that the local wisdom product and its marketing become a crucial component of social constructivism-based entrepreneurship education. The model design results in three main aspects such as general information (school identity, preliminary competency, Pancasila students' profile, facility and infrastructure, students' target, and learning materials), core competency (objective, meaningful comprehension, stimulus questions, learning process, assessment, remedial, and reflection), and attachment (students' worksheet, references, glossary, and works cited). The initial product's outcome demonstrates that every model plan and item generated falls within the